"Utterly Unknowable": Challenges to Overcoming Madness in Sarah Kane's Blasted, Crave, and 4.48 Psychosis - Peters, Margaret (Université d'Ottawa / University of Ottawa, 2016)
Sarah Kane has often been categorized as an “In-Yer-Face” playwright, part of a group of contemporary British playwrights interested in making audiences feel the outcome of violence. However, Kane’s plays have also arguably challenged many existing theatrical forms, including the late twentieth century resurgence of “Angry Young Men” plays. While critics have been quick to identify madness as a main theme of her work, few have connected each play’s complex construction of madness with a struggle to complicate existing theatrical form. Through an intersectionally feminist reading of three of her plays—Blasted, Crave, and 4.48 Psychosis—this thesis examines the connection between the rejection of normative disability tropes (or madness, more specifically) and the challenging construction of theatrical form that takes place within each of these Kane plays.
Keywords: Sarah Kane; madness; disability; narratives; Blasted; Crave; 4.48 Psychosis; gender; race; feminis*